2017
DOI: 10.1080/17518423.2017.1368730
|View full text |Cite
|
Sign up to set email alerts
|

Use of virtual reality intervention to improve reaction time in children with cerebral palsy: A randomized controlled trial

Abstract: This paper proposes VR as a promising tool into the rehabilitation process for improving reaction time in children with cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…In the study by Do et al,41 VR programs were found to be capable of changing motor skills (motor performance) in individuals with hemiplegic CP. Likewise, Pourazar et al42 showed significant improvements in a group of children with CP after an intervention program using VR.…”
Section: Discussionmentioning
confidence: 96%
“…In the study by Do et al,41 VR programs were found to be capable of changing motor skills (motor performance) in individuals with hemiplegic CP. Likewise, Pourazar et al42 showed significant improvements in a group of children with CP after an intervention program using VR.…”
Section: Discussionmentioning
confidence: 96%
“…Reaction time was assessed to evaluate the activity process of the central nervous system, such as motor preparation and motor program [ 24 ]. Using an iPad app (Reaction Test & Speed Test, Wang Haiwen), the instructor instructed patients that when the red screen became green, the screen should be touched as quickly as possible.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to our study, the trainings were held twice a week for 45 min each session and lasted 8 weeks [45]. Pourazar et al (2018) likewise examined the impact of VR intervention training on reaction times in children with cerebral palsy. The results revealed improvement in the experimental group after the VR intervention program.…”
Section: Discussionmentioning
confidence: 95%
“…Continuous variables were presented as mean ± standard deviation (SD) or median and interquartile range (IQR), where appropriate, according to the Kolmogorov-Smirnov normality test. The sample size was calculated based on previous studies according to the changes in reaction time of immersive VR with an effect size of 0.795; it was determined that 12 patients should be enrolled [26]. G*Power 3.1.9 software was used to calculate the sample size.…”
Section: Discussionmentioning
confidence: 99%